(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Soil samples from high land, medium high land, medium low land and low land of Brahmaputra Floodplain area showed that pH of the soils were slightly acidic; organic matter (OM) content was medium; total nitrogen (N), available potassium (K) and boron (B) content were low; available phosphorus (P) content was very low; available sulfur (S) and calcium (Ca) content were medium to very high; magnesium (Mg) and zinc (Zn) content were low to optimum; copper (Cu), manganese (Mn) and iron (Fe) content were very high suggesting the fact that soils of this area is moderately suitable for agricultural uses. J. Environ. Sci. & Natural Resources, 8(2): 11-14 2015